Direct imaging of orbitals in quantum materials - Yavaş, Hasan; Haverkort, Maurits W. (Nature physics, 2019)
Getting a picture of a d or f atomic orbital has been a challenge, but the X-ray scattering technique reported here enables direct transition from core s orbitals to the d orbitals so that their spatial shape can be mapped with no need for modelling.
Gesehen am 28.08.2019